Evaluasi Pemeliharaan Fisik Taman Tirta Wisata Keplaksari Kabupaten Jombang Jawa Timur - Chrisna Murthiningsih; Ni Nyoman Ari Mayadewi (Fakultas Pertanian, Universitas Udayana, 2023)
Tirta Wisata Keplaksari Park or also known as Tirta Wisata is a water tourism park located in Jombang, East Java. This study aims to determine and evaluate the physical maintenance system at Tirta Wisata. This study uses observation techniques, questionnaires, interviews, and literature studies to collect data. Questionnaires were distributed randomly to 50 respondents. Respondents perceptions of Tirta Wisata were good in terms of the cleanliness of the park from wild plants, the cleanliness of the lake, in the other hand the cleanliness of the toilets from odors is getting quite good results. Respondents of this study also suggested to add or create several facilities such as a children's playground, food court, several garden area, and an adequate parking lot. This study suggestion is to add some garden maintenance tools and materials for maintain the park and write down the garden maintenance schedule in clear and detailed so that it can be implemented properly.